Constantino J. Carvallo Alzamora, first president of the Peruvian Society of Obstetrics and Gynecology - Álvarez, Ricardo Iván (2017)
Constantino José Carvallo Alzamora, MD was the first president of the Peruvian Society of Obstetrics and Gynecology (SPOG); he significantly contributed to its normative organization and institutional stability. However, his more extensive and diverse career made him in one of the most famous Peruvian physicians of the first half of the 20th century. The medical order in general and the gynecologists in particular had a debt to this celebrity, since a biography that really approached his existence had not been written to date. Hence, the current article is not only a historical investigation, but also a well deserved act of justice.